Reviewing the Common Barriers to the Mental Healthcare Delivery in Africa - Essien, Bernice (Journal of religion and health, 2020)
The current paper sought to thematically present common challenges associated with mental healthcare services in Africa. We largely limited our search for literature materials to studies published from 2003 to 2019 in African countries from which the findings showed that there are common challenges confronting mental healthcare services in Africa. The challenges include: inadequate mental healthcare facilities, funding constraints, shortage of professional healthcare workers, inadequate training and development scheme for mental health workers and weak mental healthcare policies. Implications for policy and practice are disclosed and recommendations are stated to trigger actions to remedy the situation. This information is beneficial for researchers, policymakers, mental healthcare providers and community members who are interested in mental healthcare issues. It was concluded that in order for Africa to enjoy successful mental healthcare service, critical and enduring attention must focus on sound and enforceable government policy on mental healthcare service, provision of adequate and regular funding, availability of adequate mental healthcare facilities, provision of training and development facilities for the mental health professionals and collaboration of mental healthcare providers.